2013
DOI: 10.1371/journal.pone.0077252
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Microvascular Mechanisms of Drag Reducing Polymers: Effect on the Cell-Free Layer

Abstract: Drag-reducing polymers (DRPs) significantly increase blood flow, tissue perfusion, and tissue oxygenation in various animal models. In rectangular channel microfluidic systems, DRPs were found to significantly reduce the near-wall cell-free layer (CFL) as well as modify traffic of red blood cells (RBC) into microchannel branches. In the current study we further investigated the mechanism by which DRP enhances microvascular perfusion. We studied the effect of various concentrations of DRP on RBC distribution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…In this study, we assessed the effect of DRPs in the process of cardiac and aortic remodeling caused by hypertension and demonstrated that blood shear stress and ET-1 expression may play DRPs are long-chain, blood soluble macromolecules, which have been shown to greatly reduce frictional resistance in both turbulent and laminar flow, known as Toms effect. 13,19 DRPs were initially used in fire fighting, irrigation and petroleum pumping to reduce frictional energy losses in large pipes. Recently, these observations have been extended to the vascular system and some biological effects of DRPs have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assessed the effect of DRPs in the process of cardiac and aortic remodeling caused by hypertension and demonstrated that blood shear stress and ET-1 expression may play DRPs are long-chain, blood soluble macromolecules, which have been shown to greatly reduce frictional resistance in both turbulent and laminar flow, known as Toms effect. 13,19 DRPs were initially used in fire fighting, irrigation and petroleum pumping to reduce frictional energy losses in large pipes. Recently, these observations have been extended to the vascular system and some biological effects of DRPs have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Drag-reducing polymers (DRPs) at nM levels markedly reduce the resistance of microvascular flow, improving tissue perfusion. 222,223 Drag-reducing polymers, such as long-chain polyethylene glycol (kDa > 10 6 ), improve perfusion and reduce mortality in models of hemorrhagic shock. 224 Drag-reducing polymers thus could maintain brain perfusion despite using a volume-limited resuscitation.…”
Section: Emerging Resuscitation Agentsmentioning
confidence: 99%
“…DRP also reduce the near-wall cell-free layer increasing wall shear stress and decreasing plasma skimming at vessel bifurcations (i.e., lowering hematocrit in daughter branches of microvessels), described in vitro [12, 13] and in vivo [14] which could explain protection of the BBB. Recent studies reported that increased wall shear stress restrains expression of proinflammatory cytokines that initiate a signaling cascade leading to activation of BBB damage [15, 16]…”
Section: Discussionmentioning
confidence: 99%